The Effect of Macroeconomic Variables on Mudharabah Deposits at Bank Muamalat Indonesia for the Period 2014–2024 - Alfian Muhammad; Muhammad Amin; Khairatun Hisan; Khairun Nisa Rambe (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2025)
This study aims to analyze the effect of inflation, exchange rate, interest rate, and gross domestic product (GDP) on Mudharabah deposits at Bank Muamalat Indonesia during the period 2014–2024. Macroeconomic stability is a crucial factor influencing public investment decisions in Islamic banking products. This research employs a descriptive quantitative approach using secondary data, including quarterly financial reports of Bank Muamalat, inflation, exchange rate, and interest rate data from Bank Indonesia, as well as GDP data from the Central Bureau of Statistics. The analysis is conducted using multiple linear regression with EViews 12. The results indicate that simultaneously, inflation, exchange rate, interest rate, and GDP significantly affect Mudharabah deposits. Partially, inflation, exchange rate, and GDP have a positive effect, while the interest rate is not significant. These findings provide valuable insights for bank management in designing profit-sharing strategies and maintaining depositor confidence, as well as assisting regulators in formulating policies that are adaptive to macroeconomic conditions